Businesses, buddies and babies: Social ties and fertility at work - Lena Hensvik; Peter Nilsson (Institute for Labour Market Policy Evaluation (IFAU), 2010)
We examine the influence that co-workers' have on each other's fertility decisions. Using linked employer employee panel data for Sweden we show that female individual fertility increases if a co-worker recently had a child. The timing of births among co-workers of the same sex, educational level and co workers who are close in age is even more influential. Consistent with models of social learning we find that the peer effect for first time mothers is similar irrespective of the birth order of the co-worker's child, while for higher order births within-parity peer effects are strong but cross-parity peer effects are entirely absent. A causal interpretation of our estimates is strengthened by several falsification tests showing that neither unobserved common shocks at the workplace level, nor sorting of workers between workplaces are likely to explain the observed peer effect. We also provide evidence suggesting that peers not only affect timing of births but potentially also completed fertility, and that fertility peer influences spills over across multiple networks. Our results forward the understandings of how individual fertility timing decisions are made and suggest that social interactions could be an important factor behind the strong inter-temporal fluctuations in total fertility rates observed in many countries.
Keywords: J13; 330; Peer effects; social preferences; co-workers; Fruchtbarkeit; Soziale Beziehungen; Arbeitswelt; Soziale Wohlfahrtsfunktion; Schweden